Analisis Peran Jaksa Dalam Upaya Memulihkan Kerugian Negara Dari Kasus Korupsi - Ramadhan, Muhammad Hariyo; Pratama, Aldino Gilang; Darsono; Nasharudin; Hery Hernawan (Consensus : Jurnal Ilmu Hukum, 2022)
Because corruption is inherent in human beings as morals or morals, it is difficult to change this culture. A plan is needed to identify and address the factors driving corruption crimes. Everyone has to build good morals in themselves to deal with corruption. By violating the social and economic rights of the people, corruption has grown into an extraordinary crime. Therefore, the attempt to exterminate him should be prosecuted "in extraordinary ways" rather than "as usual". Normative Yuridis is used in this study. authority to reimburse the state's financial losses caused by corrupt criminal acts; in addition, the prosecutor also has the power to take assets derived from corrupt crime. Prosecutors should be more careful and thorough in their investigation or arrest than the Anti-Corruption Commission. The amount of funds needed to repair the state's financial losses caused by corruption must be increased. In addition, the assets held by the perpetrators must be seized, confiscated, or auctioned in exchange for the economic losses of the state. To protect damaged assets from corruption, the Asset Seizure Act must be enacted.